2021
DOI: 10.2169/internalmedicine.6795-20
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Establishment of a General Internal Medicine Department and an Increased Number of Blood Cultures in Other Departments: An Interrupted Time Series Analysis

Abstract: Objective The establishment of a department of general internal medicine (GIM) has been shown to improve the clinical outcomes among patients treated in GIM departments but the effect on practice patterns in other departments remains unclear. We evaluated the association between the establishment of a GIM department and the use of blood cultures, an indicator of quality of care of infectious diseases, in other departments. Methods This study was conducted between 2013 and 2017 in a community hospital which est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…[2] Another report showed that it was associated with an increased number of blood cultures ordered in other departments. [13] Due to the shortage of IDSs, ID and GIM physicians should cooperate to promote the quality of care and clinical management in hospitals in Japan. [14] There are some limitations that must be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Another report showed that it was associated with an increased number of blood cultures ordered in other departments. [13] Due to the shortage of IDSs, ID and GIM physicians should cooperate to promote the quality of care and clinical management in hospitals in Japan. [14] There are some limitations that must be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“… 14 The evidence supporting the clinical benefits of GM is currently limited, with most evidence regarding cost reduction and improvement in quality of care derived from small-scale, single-center studies. 15 , 16 These studies cover a range of clinical areas, including improved quality of inpatient care for infectious endocarditis, 17 increased blood culture collection rate, 18 shortened length of hospital stay, 19 improved quality of home medical care, 20 COVID-19 care, 21 compensating for the shortage of specialists, 22 and improved heart failure management. 23 Studies have been conducted on the patient population, locations, and clinical skills covered during GM training.…”
mentioning
confidence: 99%